2019
DOI: 10.1021/acs.bioconjchem.9b00240
|View full text |Cite
|
Sign up to set email alerts
|

PLGA Microspheres Coated with Cancer Cell-Derived Vesicles for Improved Internalization into Antigen-Presenting Cells and Immune Stimulation

Abstract: Microspheres (MS; 1−3 μm) with different degrees of surface roughness were prepared to assess the effects of surface topology on internalization into antigen-presenting cells (APCs; macrophages and dendritic cells). In this study, we demonstrated that the intracellular uptake of MS is readily enhanced by surface modification with nanoparticles or cancer cellderived vesicles (VE) to modulate their surface topology. MS coated with nanovesicles (MS-VE) with high surface roughness was more successfully and efficie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 41 publications
(103 reference statements)
0
9
0
Order By: Relevance
“…[ 14,15 ] Accordingly, cell‐derived VEs have been adopted as carriers and as coating materials for nanoparticles with drugs for selective drug delivery. [ 16,17 ] Recently, hybrid VEs comprising two types of cell‐derived VEs (e.g., red blood cell (RBC)–B16‐F10 hybrid membrane) and synthetic liposome/cell‐derived membranes (e.g., C6 glioma cell membranes/liposomes) have been reported for homotypic targeting and long circulation. [ 10,18 ] However, hybrid VEs comprising two types of cancer cells for dual targeting to two types of tumors have not yet been reported.…”
Section: Introductionmentioning
confidence: 99%
“…[ 14,15 ] Accordingly, cell‐derived VEs have been adopted as carriers and as coating materials for nanoparticles with drugs for selective drug delivery. [ 16,17 ] Recently, hybrid VEs comprising two types of cell‐derived VEs (e.g., red blood cell (RBC)–B16‐F10 hybrid membrane) and synthetic liposome/cell‐derived membranes (e.g., C6 glioma cell membranes/liposomes) have been reported for homotypic targeting and long circulation. [ 10,18 ] However, hybrid VEs comprising two types of cancer cells for dual targeting to two types of tumors have not yet been reported.…”
Section: Introductionmentioning
confidence: 99%
“…These studies revealed that MPLA-loaded PLGA MPs coated with cancer cells form cancer cell-derived vesicles (MS-VEs) that were more efficiently engulfed by APCs compared with noncoated microspheres. In addition, incorporation of MPLA within MS-VEs triggered elevated release of immune stimulating cytokines from macrophages and dendritic cells compared to free MPLA . Together, these studies suggest that polymer particles coated with cancer-derived cell membranes can induce efficient immune responses, and this response could be further amplified by incorporating immune signals in the core material.…”
Section: Learning From Cancer Immunotherapy To Improve Vaccine Agains...mentioning
confidence: 81%
“…This MS-VE could serve as a platform system for delivering immune stimulators and antigens to antigen-presenting cells with negligible toxicity. RNA interference (RNAi) combined with immunogenic chemotherapy can elicit potent antitumor immunity against cancer cells (Jung et al, 2019).…”
Section: Polymer-based Nanovesicle Delivery In Conjunction With Immun...mentioning
confidence: 99%